Delineating Structural Features Related to Hydrothermal Alterations for Possible Mineralization in Share Area, Kwara State Nigeria Using Aeromagnetic Data - Adebisi, Warith Adewale; Folorunso, Ismail Oluwaseye; Abubakar, Hussain Olanrewaju; Olatunji, Saminu; Olaojo, Michael Opeoluwa (Indonesian Journal of Earth Sciences, 2024)
Mineral deposits of significant economic value are abundant in the subsurface of Nigeria, presenting a promising alternative to the nations over dependence on petroleum revenues. This study interprets aeromagnetic data from Share, Kwara State, Nigeria, to delineate subsurface structural features associated with hydrothermal zones, which are key indicators for potential mineralization. The methodologies applied upward continuation, analytic signal, tilt derivative, and first vertical derivative (FVD). These offer insights into subsurface geology that can be broadly applied in geophysical exploration and mineral resource management. The results reveal structural trends predominantly in the NE–SW direction, with some NW–SE alignments, indicative of hydrothermal alterations linked to mineral deposits. The analytical signal map identified amplitude values ranging from 0.004 nT/m to 0.073 nT/m, with low and intermediate magnetic intensities linked to sediment-filled basement rocks and possible limestone and sandstone formations. High-gradient anomalies, 1.280 nT/m to 1.374 nT/m, were attributed to geological contacts, fractures, dykes, and hydrothermal vents. Depth estimates from the source parameter imaging map revealed hydrothermal and structural zones at depths ranging from 287.9 m to 1360.7 m, with deeper sources >1202.1 m indicating tectonic activity and mineralization potential. The FVD and Tilt Derivative maps further highlighted faulted zones, shear structures, and intrusive bodies with intensities between 0.031 nT/m and 0.041 nT/m, suggesting active tectonics. High magnetic anomalies in the central, northeastern, and southeastern regions were identified as prime targets for exploration, indicating magnetite-rich bodies, igneous intrusions, and hydrothermal zones. Integrated exploration strategies combining geophysical, geochemical, and structural data are recommended to refine anomaly delineation, prioritize field validation, and enhance mineralization discovery. These findings establish the Share area as a promising site for regional mineral exploration, supporting Nigeria’s diversification efforts toward sustainable resource development.